Unlearning, Relearning, and Paradigm Shift to Online Tertiary Education during the COVID-19 Pandemic in Bangladesh (Bangladesh Journal of Medical Science, 2021)
The current coronavirus disease 2019 (COVID-19) pandemic has compelled to shut down all levels of educational institutions worldwide for a particular time. The pandemic has forced educators and institutions to rapidly switching from classroom teaching to online teaching. The changes in teaching strategies have led both teachers and students into sudden multifaced challenges. Consequently, Bangladesh has closed down all classroom teaching and adapted online system education using different digital platforms. This opinion review has outlined some challenges and opportunities of online in Bangladesh as a representative of developing countries. This paper has further reviewed underlined vital factors in the university system of developing countries that may contribute to paradigm shifts in the education system in the modern competitive world.Bangladesh Journal of Medical Science Vol.20(5) 2021 p.65-71